Gestörter Film - Rein, Katharina (Büchner-Verlag, 2022)
Wes Craven’s »A Nightmare on Elm Street« (1984) enjoys cult status today more than ever. The mere thought of its main character Freddy Krueger still sends shivers down the spines of many viewers – and brings a grin to the faces of die-hard slasher fans. Katharina Rein subjects this undisputed genre classic to an intensive reading in which she traces the central moments of the disturbance. Using selected sequences from the film, she uncovers the workings of disruption in the horror genre. Contrary to widespread perceptions, she understands them, following Michel Serres, not as obstructive but as productive. As Rein shows, it is this productivity that has contributed significantly to the enduring success and film historical significance of »A Nightmare on Elm Street«.